Konut yakın çevresinin kullanıcı bilişsel duygusal ve davranışsal parametrelere bağlı olarak değerlendirilmesi - Çerçi, Serpil (Fen Bilimleri Enstitüsü, 1997)
Ortamların insan kişiliğinin gelişimindeki etkileri, insanların bu konudaki potansiyel gereksinimlerinin, beklentilerinin karşılanmasını; ve bu çevreleri oluşturan mimarlık ürünlerinin hem işlevsel, hemde görsel kalitelerinin arttırılmasını gerektirmektedir.Bu nedenle, konut ve yalan çevresinde kaliteyi oluşturan bileşenlerin geniş kapsamda ele alınması, verimli sonuçlara ulaşabilmek için psikolojik, kültürel, teknolojik ve ekonomik açıdan, toplumsal isteklerin gözönünde tutulması ve bunların doğru bir şekilde analiz edilip yönlendirilmesi büyük önem taşımaktadır. Bu bağlamda bu tezde ortaya konan ana amaçlar: Konut yalan çevresi ile ilgili kuramsal tabanı oluşturmak Konut yalan çevresi kalite ölçütlerini elde etmek amacıyla bir çerçeve model geliştirmek, Geliştirilen bu modelde ortaya konan yöntem ve teknikleri, kullanıcı değerlendirmeleri yoluyla (Adana' da), tarihsel süreç içinde gelişen geleneksel ve gelişmiş iki farklı ve nitelikteki konut çevreleri üzerinde deneyerek, analitik bir çalışma yapmak, Bu model aracılığıyla ortaya konan ölçütlerin tasarıma ve bu yöndeki çalışmalara ışık tutması için organize veri birikimini sağlamaktır. Altı bölümden oluşan çalışmanın birinci bölümünde genel anlamda kalite / nitelik olgusuna değinilmekte, mimaride kalite eksikliğinin ortaya çıkardığı ve kullanıcının hoşnutsuzluğu ile kendini gösteren sorunların tanıtılması ile bu sorunların saptanmasına ve çözümüne yönelik kuramsal çerçeve ve modellerin tasarıma yansıtılması gerekliliği konuya giriş niteliğinde ve ön bilgiler halinde sunulmaktadır. Bunlara ilaveten bu hipotezde ortaya konan problem, amaç, kapsam ve yöntem tanıtılması ile tezin kurgusu yapılmaktadır. ikinci bölümde, konut, konut çevresi ve kalite kavramlarının açıklaması yapılarak, insan-konut-çevre ilişkisi ve yapıda kalite isteminin gelişmesi ile ilgili bilgiler kısaca verilmektedir. Ayrıca fiziksel çevrenin genel kalitesinde etkili olan tasarım ve yapı üretim kalitesi ile ilgili açıklamalar yapılarak, günümüzde kaliteli ürün oluşmasında büyük etkisi olan standardlardan ve denetim gerekliliğinden söz edilmektedir. Üçüncü bölümde geçmişten günümüze kalite olgusunun karşılaştırmalı değerlendirmesi yapılmakta ve konut yakın çevresi ile ilgili olarak dünyadaki uygulamalardan çeşitli örnekler verilmektedir. Bu bölümün ikinci kısmında çalışmanın kuramsal tabanı oluşturulmakta ve birinci bölümde ortaya konan sorunların çözümüne yönelik çeşitli yaklaşımlar ve modeller özetlenmeye çalışılmaktadır. Mevcut bu modeller ve yaklaşımlar ışığında Adana kentinde yapılacak örneklem çalışmasına uygun nitelikte kavramsal çerçeveyi oluşturacak modelin kurgusu yapılmaktadır. Dördüncü ve Beşinci bölümde, oluşturulan modele dayalı olarak kullanım sonrası değerlendirmeler ile, anket çalışmasında kullanılacak değişkenler saptanmaktadır. Bu değişkenlere bağlı olarak Adana kentinde geleneksel ve gelişmiş iki bölgenin konut yalan çevresinde niteliksel sorunları saptamaya yönelik yöresel bir çalışmanın verilerini elde etmek amacıyla bir anket formu hazırlanmaktadır. Elde edilen veriler ise sözel ve sayısal olarak belirlenerek chi-square testi ve cross tabs analizi uygulaması ile ayrı ayrı değerlendirilmektedir. Sonuç bölümünü oluşturan Altıncı bölümde ise çalışmanın genel değerlendirilmesi yapılmaktadır.

The studies about domicile environment or "living quality"is going on from 1940. In the last 20 years the scientific studies and politics are developed to understand this subject more clearly. Besides physical and environmental factors, the personel and public desires must be taken in hand that's to provide the users wants to add it's very important to study about this subject. In this study Adana which is developing fast and without plan is chosen, two different developing periods in the historical time and traditional about the near environment and living quality is varified. People living in this city look for about quality, changing whish etc. it mean sentimental behaviours. When they are not satisfied, the physical manners and pleasent level are noticed. In this study,a model is farmed. This model is about the near environment of domicile quality. The techniques and methods which are taken in this model are tried about the historical time in two ways. There are traditional domicile environment which as developed and which will developed in the future. The variables varified evaluation after using and the questionare study. The datums are taken in use chi- square test and cross tabs analiysis. A meaningful relation is found between domicile user's education, economy etc. and variables knowledge, emotional, behavioural. The satisfaction and pleasment of the human changes according to the social activities, car park and open area, securty. This effects the human to change the house. IX The living environments influence the development of the human characters.That is why the architecturel products' quality has to be improved to provide human's requirements and expectations. It has a great importance of considering the comunity demands to inspect in huge scope of the factors that confirms quality in the near environment of the domiciles. In this Study which conducted the main aims are : * To advance a new plan that can be used as a criterion in the quality of near environments of the domiciles * Analyzing of the near environments of the domiciles by interpretations of the habitants using this new plan * Using these criterions in the envisagement by this plan The humans' quality expectation from the near environments of the domicile and the problems accured while realising this expectation or the level of displeasments should be determined It is obviously necessary to prove the quality of the near environments. of the domicile For this reason the habitants' quality expectation are varying according to their perception, sensetion etc. This variables of the near environments of the domicile are investigated and tryied to find out solutions by social, physical and psychological In this plan the habitants and domicile environment charecters as an objective determinant and the human characters whice act as a filter had been used as a subjective determinant. Using these determinants a correlation between the variables of the humans perception,, sensetion, behaviour had been obtained. In this way the qualty criterions of the domicile enviroment tried to explained. Tha habitants interpretations for the near environments of the domicile affect their satisfaction level, and resulted in variable behaviour levels These behaviour levels are : * Pleasment, satisfaction and preference * chancing of the behaviour and adaptation * Not to accept the environment and chancing the environment. This theoretical model of the environments by human whe will reach to the subjective and objective criterions. At the same time these criterions are the decision of the habitants whether the environment is has a quality value or not. The behaviour levels ( preferance and behaviour ) explains the responses or the reflects of the habitants agains to the environment conditions These responses affects the interpretations of the environments and reflect the quality criterions Hovever, because of the chance in the subjective and objective determinants in time will chance the decisions unavoidably. So these factors have to be considered to use the criterions in the envisagements. Regarding to above explanations the main hypothesis of the near environment of the domicile quality according to the interpretation of the environment is as follows from objective to the subjective The domicile and phsical environment charecters ( objectice determinants ) affect the interpretation of the environments by culturel and psycho - social charecters The near environment of the domicile affects the variables of human behaviours by subjective determinants The habitants charecters affect the variables of human behaviours by subjective determinants There is a continious interference between habitant and environments characters The knowledge, amotional and behavioural variables affect each other The subhypothesis are as follows of this main hypothesis XI The type, class, age, condition or situation, numbers and park place of the domicile that habitant accomodate The green field, closenes to the other buildings, open place, and the plan, regularity, upkeeping, cleaness of this open place Number of the children, number of the working household, population in the family. The avarage income, education level, ages ate. factors affects the satisfaction and pleasent of the habitants. The referred variables are in connection between habitants expectation and behavioural conditiones. For that reasons,the sensetions and behaviours of the habitants as a quality criterion should be investigated and in this case a supervision and to take a poll are necessary.. The results are discussed by models and the methods is determined by " chi - square test and cross - tabulation analysis " The opinions and interpretations of the habitants has a great importance to solve the problems that accured from the pure quality environment of the domicile. We hope that this thesis will be proceed to obtain main criterion and rules in the near environment of the domicile The data obtained from the research which carried out for quality on envisagement, and production and access will be expected to meet demands in this kind studies. Quality and qualifications are investigated generally in the first section of this study which constitued five section and the displeastments, resulted in deficiency of quality in architecture, accured problems, and the identification of these problems, the theoretical and model solutions for this problems and the necessarty of this reflectations of this solutions to the envisagements are presented as a preface and briefly. In addition in this hypotehesis, problems, scope, aim and method fiction are introduced. Xll In the second section the domicile, environments of domicile and quality terms are explained and Human, domicile, and environment relations and advances in the demands of quality domicile are introduced briefly.. Besides the qualified production building which affects the general quality of physical environmets are explained and mentioned from the standarts and controls whice has a great affect supplying of quality products in nowadays. In third section the quality criterion are interpreteted comperensivly from the past to nowaday and some examples are shown for the near environment domicile application in the world. In the second part of this section the theoritical base of this stuidy are built and some aproaches and models are summerized to solve the problems which existed in the first section.In the respect of the present plan and approaches, a therotical fiction outline is made for the best model for the city of ADANA as an experimental study. In the fourth and fifth section after used interpretations and the variables which will be used in the poll are determined according to the fictioned plan. A new public survey from has been is prepared which aimed to determine the traditional and advanced qualified problems of the two parts city of ADANA and obtain data that will show the results of a local study. The obtained data will be both alfha and numerically determined and also will be analysed both " chi square test and cross tabulation analysis " seperatly. In the last section of this study a general interpretation is done. The researches show that if a more living quality is desired, the methods for objective determinants of the environment quality and subjective determinants are needed. Not only the objective determinants but also the subjective determinants must be searched. Because of this aim to support the design studies, the variablesare chosen for having the concrete values. The relation between these variables which are chosen as dependent and independent were searched. Xlll In this study combination between a high number of variables can be made in many ways. Relation degrees can be measured. But this is accepted enoughly because of the limited program of the study. An evaluate after using was made related to the objective and subjective determinants ( behaviours, emotion and sensation of the users ) etc. In this study it's determined that the satisfaction of the near environment of the domicile in Adana is related to the physical environment conditions more than the social conditions. The most important indicators that show the environment satisfaction are education degree, domicile experience and population. These characteristics show differences according to the present domicile regions. The searched inventions and datums show that the social and physical environment quality isn't provided in the traditional domicile environment which we have chosen as an example. And also it's determined that the people have the expectation to have more and more possibility around the environment. The people look for a different living quality around the environment. They found this different living quality in the present domicile than the traditional environment domicile. In the inpreferenced regions to develop the physical environment, to advance function to present different possibilities, are invented to make the those places prefered. XIV Decision Measurament Which Design Quality Datum Basement For The Design Knowledge - Behavioural Effective Indrection Norm Effective Direct Norm Effective The Model which defines quality measuraments of housing In this study a meaningful relation between domicile and the changeables about the user ( number of the flats, education, economy Job, age, number of the children ) etc. is found. According to the inventions the human changes its domicile about the satisfaction around the environment, open area, safety car park, social activities, social relations, distance between the buildings, green area etc. In that case these variables must be considered by the director units and the projecters. If it's not considered or not advanced the conditions, the human must be educated in some personel characteristics. xv As in the 2.2.6 section the law about the domicile that's the standards about the environment, must be put in use in the other domicile. The legal arrangement must be made. In this study because of a lot of factors and the large extended subject, the aim is to see relations, research and the changeables completely. All the variables are not taken in this study a lot but in the father studies this can be a step. When the variables are applied as a group analysis more detailed informations can be taken. Also to see all the factors this study must be done. In another way it's not possible to reach all the sums but whe can have detailed analysis by the datums. As a results, the quality concept has a large content and the study has the limited content. To advance this study other studies can take a way. I wish this study will lead other studies and be used. It's thought this is an important step to advance the near environment quality.
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1997
Keywords: Adana; Bina bilgisi; Kişilik gelişimi; Konut çevreleri; İnsan-çevre etkileşimi; Adana; Building information; Personality development; Neighbourhoods; Human-environment interaction